Jurnal alam bina - Universiti Teknologi Malaysia. Fakulti Alam Bina (Fakulti Alam Bina, Universiti Teknologi Malaysia, 1998)
On environmental development studies in Malaysia.
Keywords: Environmental policy : Malaysia : Periodicals; Architecture : Malaysia : Periodicals; Architecture; Ecology; Environmental policy; Malaysia : Environmental conditions : Periodicals; Malaysia